1996
DOI: 10.1038/382595a0
|View full text |Cite
|
Sign up to set email alerts
|

Cerberus is a head-inducing secreted factor expressed in the anterior endoderm of Spemann's organizer

Abstract: An abundant cDNA enriched in Spemann's organizer, cerberus, was isolated by differential screening. It encodes a secreted protein that is expressed in the anterior endomesoderm. Microinjection of cerberus mRNA into Xenopus embryos induces ectopic heads, and duplicated hearts and livers. The results suggest a role for a molecule expressed in the anterior endoderm in the induction of head structures in the vertebrate embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
478
1
8

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 710 publications
(500 citation statements)
references
References 42 publications
13
478
1
8
Order By: Relevance
“…One of these was completely sequenced and was 84% identical to laevis Cerberus and the amino acid level. In situ hybridization analysis with tHex and tCerberus probes demonstrated that the tropicalis genes were expressed in a pattern identical to their laevis counterparts (Bouwmeester et al, 1996;Newman et al, 1997;Zorn et al, 1999). tHex is expressed in the most dorsoanterior endomesoderm of the blastula and gastrula embryo ( Fig.…”
Section: Hex and Cerberusmentioning
confidence: 95%
See 2 more Smart Citations
“…One of these was completely sequenced and was 84% identical to laevis Cerberus and the amino acid level. In situ hybridization analysis with tHex and tCerberus probes demonstrated that the tropicalis genes were expressed in a pattern identical to their laevis counterparts (Bouwmeester et al, 1996;Newman et al, 1997;Zorn et al, 1999). tHex is expressed in the most dorsoanterior endomesoderm of the blastula and gastrula embryo ( Fig.…”
Section: Hex and Cerberusmentioning
confidence: 95%
“…ac.uk/Projects/X_tropicalis/). For fil- ter screening, the full-length coding regions of X. laevis Sox17␣ (pSKSox17␣, KpnI/SacI), Sox17␤ (pSKSox17␤, EcoRI/NotI; Zorn et al, 1999), Hex (pSK-Hex, EcoRI/XhoI; Newman et al, 1997), Cerberus (pBS-Cerberus, EcoRI/XhoI; Bouwmeester et al, 1996), and Hnf3␤/FoxA2 (pCS2-XFD3, EcoRI/NotI, a gift from Dr. Knoechel), were gel-isolated, radiolabeled by random priming, and hybridized at high stringency in Church's buffer. We only pursued cDNAs and ESTs that appeared to encode full-length clones: that is, they had the putative start of translation based on the laevis sequence.…”
Section: Cdna Library Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…A secreted molecule named "Cerberus," which is expressed in anterior endoderm, has the property to induce ectopic head structures when microinjected into ventral regions of Xenopus embryos (Bouwmeester et al, 1996;Bouwmeester, 1997). The patterning of the chick forebrain anlage by the prechordal plate has been described by Pera and Kessel (1997).…”
Section: Influence Of Sickle Endoblast On Neurulation and Gastrulationmentioning
confidence: 99%
“…For FGF8, endocytosis regulates the amount of extracellular protein available for signaling, and the distance the protein can travel from the source of production (Scholpp and Brand, 2004). Receptor availability and extracellular antagonists are powerful dynamic regulators of morphogen gradients (Smith and Harland, 1992;Sasai et al, 1994;Bouwmeester et al, 1996;Goodrich et al, 1996;Meno et al, 1996Meno et al, , 1999Thisse and Thisse, 1999;Cheng et al, 2000;Tanegashima et al, 2000;Larrain et al, 2001;Branford and Yost, 2002;Chang et al, 2003;Harms and Chang, 2003;Zhang et al, 2004). In addition, the preferential degradation of a particular mRNA can contribute to formation of a morphogen gradient.…”
Section: Introductionmentioning
confidence: 99%